Strategi Pembelajaran Guru Al-Qur’an Hadits dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa di MTs An-Nur Palangka Raya - Noterisa, Siti; Hartati, Zainap; Mahmudah, Istiyati (Kamaya: Jurnal Ilmu Agama, 2025)
There are still many students in the madrasah who do not possess the ability to read the Al-Qur’an well and correctly. Therefore, appropriate teaching strategies from Al-Qur’an Hadith teachers are needed to develop this skill. This study aims to describe the strategies used by Al-Qur’an Hadith teachers in improving the reading skills of the Al-Qur’an among seventh-grade students at MTs An-Nur Palangka Raya. The method used is qualitative descriptive, with data collection techniques through observation, interviews, and documentation. The results show that teachers apply the Iqra’ method with a direct, individual, modular, CBSA (Active Student Learning) approach, and peer assistance. This strategy has proven effective in enhancing students' reading fluency. However, there are obstacles such as a lack of motivation, minimal parental support, and limited learning time. To address these challenges, teachers implement personal and collaborative approaches. In conclusion, the learning strategy using the Iqra’ method contributes positively and gradually to the improvement of students' Al-Qur’an reading abilities. This research is expected to serve as a reference for the development of more effective Al-Qur’an teaching methods in madrasahs.